Real effects of earnings stripping rules - Lisa De Simone; Henning Giese; Reinald Koch; Christoph Rehrl (Arbeitskreis Quantitative Steuerlehre (arqus), 2025)
This study examines the real effects of earnings stripping rules introduced in the European Union in 2019, which tie interest deductibility to contemporaneous profitability. Exploiting a quasi-natural experiment created by the EU's harmonized implementation under the Anti-Tax Avoidance Directive and using a difference-in-differences design, we analyze consolidated data from 3,312 firms across 22 EU Member States from 2012 to 2023. We find that earnings stripping rules significantly reduce operational risk-taking, investment, and innovation, consistent with profit-contingent deductibility lowering the expected debt tax shield in low-profit years. These effects are particularly pronounced among firms with high pre-reform operating risk, which also experience slower growth and a higher likelihood of financial distress following the reform. This study contributes to the literature on corporate taxation and risk-taking, showing that profit-linked interest limitations have real effects and underscoring the importance of rule design in balancing anti-avoidance objectives with investment and innovation.
Keywords: G32; G33; H25; H26; H87; 330; corporate risk-taking; capital structure; asymmetric taxation; earnings stripping rule